Sustained antitumor response to lenvatinib with weekend-off and alternate-day administration in chemotherapy-refractory thymic carcinoma: a case report. Issue 4 (5th April 2023) - Sunaga, Noriaki; Miura, Yosuke; Sakurai, Reiko; Ohshima, Sohei; Uno, Shogo; Muto, Sohei; Sato, Mari; Tsurumaki, Hiroaki; Yatomi, Masakiyo; Koga, Yasuhiko; Ohtaki, Yoichi; Nagashima, Toshiteru; et al.
Abstract : Lenvatinib is a multitargeted kinase inhibitor and maintaining its dose intensity has been shown to be beneficial in patients with thyroid and hepatocellular carcinomas. However, most patients require lenvatinib interruption and dose reduction due to the high incidence of adverse events (AEs). Lenvatinib was recently approved in Japan for patients with unresectable thymic carcinoma; however, real-world evidence of its clinical benefit is limited. Here, we report the case of chemotherapy-refractory thymic carcinoma in a patient who was administered a starting dose of lenvatinib using a 5-day on/2-day off (weekend-off) protocol, followed by alternate-day administration after fatigue onset derived from overt or subclinical hypothyroidism. Consequently, the patient exhibited a durable response to lenvatinib, with a 17-month progression-free survival without any severe or intolerable AEs. The present case suggests that maintaining lenvatinib dose intensity using such alternative administration regimens contributes to favorable clinical outcomes in thymic carcinoma.